Draft Annual Plan 1994-95 Andhra Pradesh Volume-II (Sectoral Programmes) 7. Social Services; Education, Sports, Art and Culture, Information and Publicity - Planning Commission (Planning Commission, 1994)
The State Council is the focal point for planning and co-ordination of Higher Education at the State Level and a liaison between the State Government and the University Grants Commission. The Council co-ordinates State Level Programmes with those of UGC’s and assists the Universities in preparing developmental programmes and getting financial assistance both from the State & Central Governments. The State Council conducts Common Entrance Examinations for admissions into Professional courses viz., Engineering, Agriculture, Medical, Law, B.Ed., B.P.Ed/M.P.Ed., courses in the State.
Finance and Planning (Plg. Wing) Department, Government of Andhra Pradesh